2000
DOI: 10.1007/s003590050431
|View full text |Cite
|
Sign up to set email alerts
|

Octopamine modulates the sensitivity of silkmoth pheromone receptor neurons

Abstract: Effects of octopamine and its antagonist epinastine on electrophysiological responses of receptor neurons of Antheraea polyphemus specialised to the pheromone components (E,Z)-6,11-hexadecadienyl acetate and (E,Z)-6,11-hexadecadienal were investigated. Injections of octopamine and epinastine into the moths had no effect on the transepithelial potential of the antennal-branch preparation nor on the spontaneous nerve impulse frequency in either type of receptor neuron. However, in the presence of continuous low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 0 publications
2
53
0
Order By: Relevance
“…observed in other species of moths such as A. ipsilon (Gadenne et al 1993), Spodoptera litoralis (Boisduval) (Martel et al 2009) and Mamestra brassica (L.) (Pophof 2000). In these species, this has been attributed to the maturation of the ORNs (Martel et al 2009), changes in hemolymph titers of the juvenile hormone (Gadenne et al 1993;Gadenne & Anton 2000) and neuromodulation of biogenic amines that act on ORNs sensitivity (Pophof 2000;Grosmaitre et al 2001).…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…observed in other species of moths such as A. ipsilon (Gadenne et al 1993), Spodoptera litoralis (Boisduval) (Martel et al 2009) and Mamestra brassica (L.) (Pophof 2000). In these species, this has been attributed to the maturation of the ORNs (Martel et al 2009), changes in hemolymph titers of the juvenile hormone (Gadenne et al 1993;Gadenne & Anton 2000) and neuromodulation of biogenic amines that act on ORNs sensitivity (Pophof 2000;Grosmaitre et al 2001).…”
Section: Figmentioning
confidence: 94%
“…In these species, this has been attributed to the maturation of the ORNs (Martel et al 2009), changes in hemolymph titers of the juvenile hormone (Gadenne et al 1993;Gadenne & Anton 2000) and neuromodulation of biogenic amines that act on ORNs sensitivity (Pophof 2000;Grosmaitre et al 2001). These 3 mechanisms could explain the results observed in C. decolora as well; however studies are needed on these variables for this species.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, the exogenous administration of both OA and 5-HT increased AL neuron sensitivity of mated males. It was previously shown that OA affects the excitability of ORNs (Grosmaitre et al, 2001;Pophof, 2000;Pophof, 2002). Furthermore, indirect evidence shows that OA can increase the sensitivity of central olfactory neurons in the context of olfactory learning; OA has been shown to stimulate protein kinases A and C, which will in turn regulate the olfactory system by phosphorylating different target proteins (Farooqui, 2007;Müller and Hildebrandt, 1995).…”
Section: Oa and 5-ht Modulate Sex Pheromone Response Characteristicsmentioning
confidence: 96%
“…OA was shown to play a role in the sexual behaviour of male moths by improving pheromone blend discrimination and orientation towards pheromone sources (Linn et al, 1996;Linn and Roelofs, 1986;. It has also been shown to have an effect on ORNs by enhancing the antennal response to pheromone through the modulation of the trans-epithelial potential of olfactory sensilla (Dolzer et al, 2001;Grosmaitre et al, 2001;Pophof, 2000), but not to plant odours (Pophof, 2002). At the central level, OA has been shown to be the responsible transmitter within the reinforcement pathway during associative learning of the honeybee (Farooqui et al, 2003;Hammer, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, neuromodulation can decrease the threshold stimulus required for generating both action potentials and behavioral responses. For example, in the male silkworm moth (Antheraea polyphemus) octopamine enhances the sensitivity of neurons that detect pheromones (Pophof, 2000). This change in receptor sensitivity correlates with the increased behavioral sensitivity seen in males of several other moth species after octopamine injection (Linn and Roelofs, 1986;Linn et al, 1992Linn et al, , 1996.…”
mentioning
confidence: 95%